2020
DOI: 10.3897/ap.2.e0781
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence as a Driving Force in the Study of Foreign Languages in Higher Education

Abstract: The study of foreign languages in the era of the third millennium is perhaps one of the most important, life-affirming competencies for the modern man. One of the effective ways to maintain motivation among university students to learn a foreign language, do their language tasks and attend practical language classes is to establish a special emotional connection with the student, i.e. to activate emotional intelligence in the process of L2 learning and the teacherstudent interaction. The main goal of this rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In a previous study, metacognitive, affective, and social learning techniques were found to contribute positively to English language proficiency. Another study discovered a relatively high positive association between EI and writing ability ( Guslyakova and Guslyakova, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, metacognitive, affective, and social learning techniques were found to contribute positively to English language proficiency. Another study discovered a relatively high positive association between EI and writing ability ( Guslyakova and Guslyakova, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study were consistent with the prior literature. A study discovered that there was a rather high positive link between EIC and writing ability ( Guslyakova and Guslyakova, 2020 ). The findings revealed that emotional intelligence and linguistic achievement are inextricably linked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active role of the student is aided by the help of the teacher for the optimal development of the communication process. It is recognised that communication is related to the psycholinguistic side of the student, which contributes to high quality teaching and enhances results, applying emotional intelligence (Guslyakova & Guslyakova, 2020). It has been noted that the quantity of students in Algerian universities has risen lately; offering quality education remains equally significant.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, it is all about achieving a high-quality level of teaching and this is attained through a great deal of effort from both sides: the teacher as the person responsible for transmitting the information and the student as the recipient of it. The teacher can provide socioemotional support (Guslyakova & Guslyakova, 2020), innovation of education, discipline, incorporation of technology, individual tutoring and small learning groups to facilitate processes in the learning of critical subjects which are fundamentally important (IESALC, 2020), and the student must co-operate -otherwise, the communication system undoubtedly fails and the overall process does not have the desired impact. Students must find a way to connect to the online classes, or at least receive the emails and act upon them accordingly.…”
Section: Limitations Of Distance Learning In Algeriamentioning
confidence: 99%